A coming-of-age story: adult neurogenesis or adolescent neurogenesis in rodents? - Arellano, Jon I.; Duque, Alvaro; Rakic, Pasko (Frontiers in Neuroscience, 2024)
It is surprising that after more than a century using rodents for scientific research, there are no clear, consensual, or consistent definitions for when a mouse or a rat becomes adult. Specifically, in the field of adult hippocampal neurogenesis, where this concept is central, there is a trend to consider that puberty marks the start of adulthood and is not uncommon to find 30-day-old mice being described as adults. However, as others discussed earlier, this implies an important bias in the perceived importance of this trait because functional studies are normally done at very young ages, when neurogenesis is at its peak, disregarding middle aged and old animals that exhibit very little generation of new neurons. In this feature article we elaborate on those issues and argue that research on the postnatal development of mice and rats in the last 3 decades allows to establish an adolescence period that marks the transition to adulthood, as occurs in other mammals. Adolescence in both rat and mice ends around postnatal day 60 and therefore this age can be considered the onset of adulthood in both species. Nonetheless, to account for inter-individual, inter-strain differences in maturation and for possible delays due to environmental and social conditions, 3 months of age might be a safer option to consider mice and rats bona fide adults, as suggested by The Jackson Labs.